تحديات قيام سياسة خارجية أوربية موحدة ومؤثرة - مجدان, محمد (revue mofakir, 2018)
Although the European Union has become a super power in the economic, commercial, financial and technological fields, It is still very weak in the political one. This is due to many challenges. This study focuses on the challenges facing this union from playing an influential role in world politics, before that, it analyses the common European foreign policy; its emergence and development, its interests and how it is made. The study takes the position and policy of the European Union towards the Arab-Israeli Conflict & the Palestinian problem , as a case study to show the European weakness & limit in foreign policy .